Plate with holes as shear connector in cold formed steel composite beams - O. P. AGUIAR; R. B. CALDAS; F. C. RODRIGUES; H. N .BELLEI (Revista IBRACON de Estruturas e Materiais, 2019)
Abstract In search of an improved compatibility between cold-formed steel profiles and precast floor systems, this study proposes an alternative shear connector for cold-formed steel-concrete composite beams. This connector consists of a steel plate with holes placed longitudinally in the middle of the upper flange of the steel profile, aiming to maximize the support area for precast slabs during the assembly. The proposed solution was experimentally tested on I-beams under bending, composed by two cold-formed steel channels, connected to a reinforced concrete slab by the shear connector. The relative slip between the steel profile and concrete, vertical deflection of the beam, and strains at several locations of the composite section were measured. The results show that the proposed connector assures shear transfer at the interface of the composite section components and shows strength of the same magnitude as other commonly used connectors.